Development of Image Series Media in Text Descriptive to Improve English Speaking Skills - Ernaeni Ernaeni; Herpratiwi Herpratiwi; Muhammad Sukirlan (UNDIKMA, 2023)
Speaking skills are seen as a very important skill to be understood by learners of a language. This is related to the function of language as a means of communication which requires its users to be able to use the language in real communication. The implication of this is that teachers should be able to create a learning environment that is able to facilitate learners to practice functional expressions actively and communicatively. Meanwhile, speaking skill is considered as one of the language skills that is used as a benchmark in determining the quality of ability. This research uses the method of methods (SLR). regarding research methods: